Plz help me to select correct option
Use the Initial Value Theorem (scroll down).
I have solved it with initial value theorem , kindly cross check it
s^2 (s^-1+10s^-2) / s^3 (1+s^-2+4s^-3)
now sF(s)
i am left with
(s^-1+10s^-2) / s^3 (1+s^-2+4s^-3)
and now putting s--->infinity
0/1= 0
so x(0) = 0 Is this correct answer plz tell me
You have the correct answer, but I'm not so sure about your method. You must compute
$\displaystyle \lim_{s\to\infty}\frac{s(s+10)}{s^{3}+s+4}=\lim_{s \to\infty}\frac{s^{2}+10s}{s^{3}+s+4}=\lim_{s\to \infty}\frac{s^{-1}+10s^{-2}}{1+s^{-2}+4s^{-3}}.$
Now you can conclude what you concluded.